제 5~7기(2010-2016) 국민건강영양조사 자료를 활용한 한국 청소년의 흡연 실태와 관련요인 연구 - 정은주; Eun-ju Jung; 송애희; Ae-hee Song; 윤혜정; Hye-jeong Youn (Han'guk Ch'iwisaeng Hakhoe chi, 2018)
Objectives: The purpose of this study was to investigate the smoking status and related factors among adolescents in Korea. Methods: We used data from the 5-7th Korea National Health and Nutrition Examination Survey. The distribution of smokers and smoking status according to general characteristics was analyzed using complex chi-square tests. Multiple logistic regression was used to analyze the relationship between smoking experience and general characteristics by calculating the 95% confidence intervals. Results: There were 618 subjects who had experience smoking one or two puffs, the starting age of one or two puffs on smoking was 14.37 years old, the number of smoking days per month was 12.42 days, and the amount of smoking per day in a month was 7.59. Gender, residential area, income level, drinking experience, subjective health status, perceived stress level, continuous depression for more than 2 weeks, suicidal thoughts within a year, and age were significantly related to smoking experience. Conclusions: It is necessary to understand the smoking behavior of adolescents. It is important to lower the smoking rate among adolescents through the development and operation of systematic smoking prevention and smoking cessation policies at the national level, as well as the efforts of youth themselves to quit smoking.